THE DEVELOPMENT OF AN AUGMENTED REALITY TECHNOLOGY APPLICATION USING ADDIE MODEL ON PACKAGING - Nafisah Mat Nasir; Noor Azly Mohammed Ali (International Journal of Accounting, Finance and Business, 2022)
This research discusses Augmented Reality (AR) technology applications that we use to incorporate virtual information into the physical world. Due to the recent development of technology, augmented reality is commonly found to be one of the interactive experiences of a real-world environment refers to the objects being augmented. Augmented Reality (AR) has emerged as a new trend technology not only in gaming applications but also in product packaging. Indeed, augmented reality has numerous applications in the packaging industry nowadays. This technology can provide numerous benefits, including improving product packaging, increasing brand loyalty, attracting new customers, and differentiating product packaging from competitors. However, it is less focused on integrating the development of AR specific on the packaging due to the lack of academic studies in the field of AR packaging. Other than that, there is no standard design process for visual interfaces with augmented reality even though there are many success stories about the use of AR by brands that have been highlighted in technology reviews from other countries but are very reluctant in Malaysia. This study will discuss the role of augmented reality in packaging and determine the process of augmented reality development on the packaging. At the end of this research, we suggest a research framework to initiate the development of Augmented Reality technology applications using the ADDIE model on the packaging. A qualitative method has been used to collect data, where a survey through a closed-ended questionnaire instruments interviews with three experts especially in creative industry. Interview results, showed that the packaging product suitable to implement with AR technology as a prototype was food and beverages industry example Bee Honey product packaging. For future studies, it is expected that will assist researchers, creative industry practitioners, and packaging product marketers that will bring better improvement and implement augmented reality on the packaging by using this framework.